A high-performance low-voltage current-mode min/max circuit. Issue 4 (6th July 2015) - Chavoshisani, Reza; Moaiyeri, Mohammad Hossein; Hashemipour, Omid
Abstract : Purpose: – Current-mode approach promises faster and more precise comparators that lead to high-performance and accurate winner-take-all circuits. The purpose of this paper is to present a new high-performance, high-accuracy current-mode min/max circuit for low-voltage applications. In addition, the proposed circuit is designed based on a new efficient high-resolution current conveyor-based fully differential current comparator. Design/methodology/approach: – The proposed design detects the min and max values of two analog current signals by means of a current comparator and a logic module. The comparator compares the values of the input current signals accurately and generates two digital control signals and the logic module determines the min and max values based on the controls signals. In addition, an accurate current copy module is utilized to copy the input current signals and convey them to the comparator and the logic module. Findings: – The results of the comprehensive simulations, conducted using HSPICE with the TSMC 90 nm CMOS technology, demonstrate the high-performance and robust operation of the proposed design even in the presence of process, temperature, input current and supply voltage variations. For a case in point, for 5 μ A differential input current the average propagation delay and power consumption of the proposed circuit are attained as 150 ps and 150 µ W, respectively, which leads to more than 64 percent improvement in terms of power-delay product as compared with the most efficient design, previously presented in the literature. Originality/value: – A new efficient structure for current-mode min-max circuit is proposed based on a novel current comparator design which is accurate, high-performance and robust to process, voltage and temperature variations.